2019
DOI: 10.3329/bjms.v18i3.41614
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Semen Samples Before and After ‘Swim Up’ Technique with Mitotracker

Abstract: Objectives: Infertility problems are seen in nearly 15% of married couples, and almost 50% of these involve male infertility. The sperm mitochondrion plays an important role in sperm motility. The morphology of sperm, sperm preparation techniques, and the number and motility of sperm during insemination are important parameters that affect the rate of pregnancy with intrauterine insemination. The aim of the study was to observe the changes in sperm mitochondrial activities and numbers with the Mito Tracker Red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…At the animal level, the body weights of RSV-treated mice indicate the biosafety of RSV (Figure 1c), which has been confirmed in many other published reports (Karabekir & Özgörgülü, 2020;Kiskova et al, 2017). Notably, the current clinical trials demonstrate that RSV was well tolerated (Berman et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…At the animal level, the body weights of RSV-treated mice indicate the biosafety of RSV (Figure 1c), which has been confirmed in many other published reports (Karabekir & Özgörgülü, 2020;Kiskova et al, 2017). Notably, the current clinical trials demonstrate that RSV was well tolerated (Berman et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, 60 μM of RSV could decrease the migration rate by approximately 70%, indicating the high efficacy of RSV's antimigration activity and its potential for further drug development (Figure 1a,b). At the animal level, the body weights of RSV‐treated mice indicate the biosafety of RSV (Figure 1c), which has been confirmed in many other published reports (Karabekir & Özgörgülü, 2020; Kiskova et al, 2017). Notably, the current clinical trials demonstrate that RSV was well tolerated (Berman et al, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…In a research on semen analysis using the 'Swim Up' Technique with Mitotracker showed that mitochondrial activity can detect a healthy sperm count. 21 This study found that the mean level of testosterone in all men was within below normal limits. Men with bilateral UDT had a mean testosterone score that was significantly lower than men without UDT, but it was not significantly different from men with unilateral UDT.…”
Section: Reproductive Hormones and Semen Analysismentioning
confidence: 60%
“…In the books of traditional medicine, there are positive effects of Nettles and Alyssum on fertility, especially males. The results of a study showed that Nettle plant extract significantly reduced the number of abnormal and dead sperm in diabetic rats and increases sperm motility 21 . The results of the case report study indicated a significant improvement in the spermogram indicators (number, motility and morphology) with use of a traditional combined medicine, which Alyssum was one of its ingredients 25 .…”
Section: Discussionmentioning
confidence: 99%